Diagnostic accuracy and limit of detection of ten malaria parasite lactate dehydrogenase-based rapid tests for Plasmodium knowlesi and P. falciparum - Tan, Angelica F.; Sakam, Sitti Saimah binti; Rajahram, Giri S.; William, Timothy; Abd Rachman Isnadi, Mohammad Faruq; Daim, Sylvia; Barber, Bridget E.; Kho, Steven; Sutherland, Colin J.; Anstey, Nicholas M.; Yerlikaya, Seda; van Schalkwyk, Donelly A.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Plasmodium knowlesi causes zoonotic malaria across Southeast Asia. First-line diagnostic microscopy cannot reliably differentiate P. knowlesi from other human malaria species. Rapid diagnostic tests (RDTs) designed for P. falciparum and P. vivax are used routinely in P. knowlesi co-endemic areas despite potential cross-reactivity for species-specific antibody targets. Ten RDTs were evaluated: nine to detect clinical P. knowlesi infections from Malaysia, and nine assessing limit of detection (LoD) for P. knowlesi (PkA1-H.1) and P. falciparum (Pf3D7) cultures. Targets included Plasmodium-genus parasite lactate dehydrogenase (pan-pLDH) and P. vivax (Pv)-pLDH. Samples were collected prior to antimalarial treatment from 127 patients with microscopy-positive PCR-confirmed P. knowlesi mono-infections. Median parasitaemia was 788/µL (IQR 247-5,565/µL). Pan-pLDH sensitivities ranged from 50.6% (95% CI 39.6–61.5) (SD BIOLINE) to 87.0% (95% CI 75.1–94.6) (First Response® and CareStart™ PAN) compared to reference PCR. Pv-pLDH RDTs detected P. knowlesi with up to 92.0% (95% CI 84.3-96.7%) sensitivity (Biocredit™). For parasite counts ≥200/µL, pan-pLDH (Standard Q) and Pv-pLDH RDTs exceeded 95% sensitivity. Specificity of RDTs against 26 PCR-confirmed negative controls was 100%. Sensitivity of the 6 highest performing RDTs were not significantly different when comparing samples taken before and after (median 3 hours) antimalarial treatment. Parasite ring stages were present in 30% of pre-treatment samples, with ring stage proportions (mean 1.9%) demonstrating inverse correlation with test positivity of Biocredit™ and two CareStart™ RDTs. For cultured P. knowlesi, CareStart™ PAN demonstrated the lowest LoD at 25 parasites/µL; LoDs of other pan-pLDH ranged from 98 to >2000 parasites/µL. Pv-pLDH LoD for P. knowlesi was 49 parasites/µL. No false-positive results were observed in either P. falciparum-pLDH or histidine-rich-protein-2 channels. Selected RDTs demonstrate sufficient performance for detection of major human malaria species including P. knowlesi in co-endemic areas where microscopy is not available, particularly for higher parasite counts, although cannot reliably differentiate among non-falciparum malaria.